Size-resonance effect in cylindrical superconducting nanowire - Croitoru, Marin (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2007)
We investigate the dependence of the basic superconducting quantities - the order parameter, energy gap and critical temperature - on the quantum confinement of a nanoscale superconductor in the clean limit. The Bogoliubov-de Gennes equations are solved numerically for a Pb nanowire in the clean limit with cylindrical cross section. Strong size superconducting resonances are found in the critical temperature of a Pb nanowire.